Transporte electrónico en conductores con nanoporos y la presencia de moléculas - Aslla, A. P. (2013)
In this work, we analyze the electron transport in rectangular conductors in which we insert a nanopore which restrict the carrier flux. Actually, to setup molecules at middle of the nanopore, we observe resonances and anti-resonances in the transmission coefficient when the molecule orientation is parallel or perpendicular to carrier flux. In our case, the conductor is described by a tight binding approximation, the transmission coefficients through the system are calculated by Landauer formula considering a ballistic regime at low temperatures and the out of equilibrium Green functions to permit us calculate the coupling of the leads with conductor including the nanopore and the molecules, recursively. The presence of the molecules at middle of the nanopore are described, also, by the tight binding approximation.